Synthesis of large-area multilayer hexagonal boron nitride for high material performance - Kim, Soo Min; Hsu, Allen; Park, Min Ho; Chae, Sang Hoon; Yun, Seok Joon; Lee, Joo Song; Cho, Dae-Hyun; Fang, Wenjing; Lee, Changgu; Palacios, Tomas; Dresselhaus, Mildred; Kim, Ki Kang; et al. (NATURE PUBLISHING GROUP, 2015)
Although hexagonal boron nitride (h-BN) is a good candidate for gate-insulating materials by minimizing interaction from substrate, further applications to electronic devices with available two-dimensional semiconductors continue to be limited by flake size. While monolayer h-BN has been synthesized on Pt and Cu foil using chemical vapour deposition (CVD), multilayer h-BN is still absent. Here we use Fe foil and synthesize large-area multilayer h-BN film by CVD with a borazine precursor. These films reveal strong cathodoluminescence and high mechanical strength (Young's modulus: 1.16 +/- 0.1 TPa), reminiscent of formation of high-quality h-BN. The CVD-grown graphene on multilayer h-BN film yields a high carrier mobility of similar to 24,000 cm(2)V(-1) s(-1) at room temperature, higher than that (similar to 13,000(2)V(-1) s(-1)) with exfoliated h-BN. By placing additional h-BN on a SiO2/Si substrate for a MoS2 (WSe2) field-effect transistor, the doping effect from gate oxide is minimized and furthermore the mobility is improved by four (150) times.
Keywords: WAFER-SCALE; GRAPHENE FILMS; LAYER MOS2; MONOLAYER; GROWTH; CU(111); NI(111)